A Psychiatric-Specific Entrustable Professional Activity for the Evaluation of Prospective Psychiatric Residents: Towards a National Standard - Benjamin T. Griffeth; W. Bogan Brooks; Adriana Foster (Association of American Medical Colleges, 2017)
Introduction Entrustable professional activities (EPAs) were developed as a way to ensure adequate skills of the medical school graduate. While the 12 EPAs apply to all medical specialties, EPA 1, "Gather a history and perform a physical examination," applies most explicitly to psychiatry through the performance of a mental status exam. Although proficiency in performing a psychiatric interview and mental status exam evolves throughout a psychiatrist's professional life, basic proficiency is essential in order to function as a psychiatry intern. We developed a tool for assessing the mental status exams conducted by future psychiatry residents. Methods Our tool contains both a video of a psychiatrist interviewing a patient and a mental status exam rating sheet that can be used when students present a mental status exam orally or in writing. We incorporated feedback from psychiatry educators at an annual meeting of the Association for Medical Student Educators in Psychiatry, followed by the reiteration of the video and the rubric. Subsequently, the rubric was verified on the performance of a cohort of 13 third- and fourth-year medical students from three institutions. Results In their mental status exam presentations, students covered all the items measured by the rubric. There was a significant difference between the third- and fourth-year medical students in describing the cognitive exam. Discussion Overall, our tool offers an opportunity to standardize mental status presentations by senior medical students who wish to specialize in psychiatry.